How brightly does the glasma shine?: photon production off-equilibrium - Berges, Jürgen; Reygers, Klaus; Tanji, Naoto (Arxiv, 2017)
We present a parametric estimate of photon production at early times in heavy-ion collisions based on a consistent weak coupling thermalization scenario. We quantify the contribution of the off-equilibrium Glasma phase relative to that of a thermalized Quark-Gluon Plasma. Taking into account the constraints from charged hadron multiplicity data, the Glasma contribution is found to be significant especially for large values of the saturation scale.
Gesehen am 22.11.2017